International criminal justice: a dialogue between two cultures - Teles, Patrícia Galvão (2017)
The implementation of the idea that individuals, wherever they are and regardless of their official status, may be accountable for crimes against humanity breaks away from the Westphalian paradigm that each State is responsible for prosecuting (or not) its citizens. After the Cold War, several international criminal jurisdictions were created, namely the ad hoc courts for the former Yugoslavia and for Rwanda and a permanent criminal jurisdiction, the International Criminal Court (ICC). Power no longer serves as a means for impunity in the same way. Those leaders involved in conflicts have learned to fear international criminal justice as a “sword of Damocles”. On the other hand, the creation of international criminal jurisdictions has become a means to consolidate peace in post-conflict situations so as to restore justice.